Optimized Energy Storage System Configuration for Voltage Regulation of Distribution Network With PV Access - Li, Qiang; Zhou, Feijie; Guo, Fuyin; Fan, Fulin; Huang, Zhengyong (Frontiers in Energy Research, 2021)
With the large-scale grid integration of wind power, PV and other renewable energy, how to guarantee voltage stability of the power system under the fluctuation of renewable energy output and make full use of renewable energy have become urgent problems. This paper proposes an optimization algorithm to determine the location and size of ESS while considering voltage stability. First, the structure of the distributed network and the models of components are introduced. Then the optimization model of ESS location of distribution network aiming at voltage regulation is established. In this step, an improved multi-objective particle swarm optimizer is presented. The algorithm guides the value of inertia weight according to the distance between the particle and the optimal particle of the population, so that the inertia weight of each particle can be adjusted adaptively, and the cross mutation operation is introduced when the distance between them is small, so as to avoid falling into the local optimal solution. At the same time, the dynamic dense distance arrangement is used to update the non-inferior solution set and guide the selection of the global optimal solution of the population, so as to keep the same solution set scale. The distribution of the solution is more uniform. In order to avoid the influence of decision maker's preference on the final result, the sequential preference method based on information entropy is used to select the optimal access scheme of energy storage from the optimal Pareto solution set. Finally, this paper optimizes the location and size of ESS under the constraints of the voltage stability based on the IEEE 24 node system. Results show that the optimal configuration of ESS can improve voltage stability; moreover, it can also provide emergency power supportability of the power system in a short-circuit fault state.